THE CONCEPT OF ECONOMIC AND SOCIAL MOBILITY, ITS SOCIOLOGICAL NATURE AND THEORETICAL FOUNDATIONS - Zakirjon Mominov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
practical potential opportunities and criteria of economic and social mobility in migration processes, employment of migrants, classification of transformation of economic and social mobility, level of urbanization, spread of professions, social speed and distances of mobility, level of economic and social updates in the labor market, demographic, economic and social of migrants The need to study qualitative sociological research issues of stratification and change trends in the mobility system, the level and direction of competition between jobs created by the state and jobs created by the private sector is an urgent issue of today.